N-butyl alcohol gas sensor composite material as well as preparation and use methods thereof

By using CoSnO3-In2O3 composite material, the problems of low detection sensitivity and poor selectivity of n-butanol gas in the prior art are solved, and the detection of n-butanol gases with high sensitivity, low detection limit and high selectivity are achieved.

CN119757476AActive Publication Date: 2025-04-04NORTHEASTERN UNIV CHINA

Patent Information

Application Number
CN202510258942.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

In the prior art, when detecting n-butanol gas, the sensitivity is low, the selectivity is poor, and the response value is not significantly improved.

Method used

The CoSnO3-In2O3 composite material was used to prepare the CoSnO3 precursor and the In2O3 precursor were synthesized by a one-step hydrothermal method. After mixed grinding and calcining, the CoSnO3-In2O3 heterostructure composite material was prepared.

Benefits of technology

High sensitivity, low detection limit and high selectivity detection of n-butanol gas are achieved, with the lower detection limit of 20ppb and the detection range is 20ppb~400ppm, and the performance is better than the n-butanol sensors reported so far.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119757476A_ABST
    Figure CN119757476A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of gas sensors, and particularly relates to an n-butyl alcohol gas sensor composite material and a preparation and use method thereof. In the prior art, the response effect of single In2O3 and CoSnO3 on n-butyl alcohol is not ideal. A precursor CoSn (OH) 6 is prepared from an aqueous solution of cobalt sulfate and sodium stannate, a precursor In (OH) 3 is prepared from an aqueous solution of indium nitrate through a hydrothermal reaction, the CoSn (OH) 6 and the In (OH) 3 are mixed, ground and calcined, and the CoSnO3-In2O3 composite material is obtained. A sensor prepared from the composite material has high sensitivity, good selectivity and repeatability to n-butyl alcohol at 250 DEG C, the detection limit is as low as 20 ppb, and the sensor has good practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas sensors, and in particular relates to a n-butanol gas sensor composite material and a preparation and use method thereof. Background Art

[0002] n-Butanol is a colorless, transparent, volatile organic compound with a pungent odor, and is widely used in industrial production. If a person inhales high concentrations of n-butanol vapor for a long time, he or she may experience respiratory irritation, coughing, chest tightness and other discomfort symptoms. Therefore, it is very necessary to monitor the concentration of n-butanol effectively and in real time. Metal oxide semiconductor sensors have become the first choice for detecting toxic and harmful gases due to their simple operation, low cost and easy real-time monitoring.

[0003] Indium oxide (In2O3) is a typical n-type semiconductor with a wide direct band gap between 3.0eV and 3.5eV. It has the characteristics of high conductivity, rich defects, adjustable shape and size, and large specific surface area, so it is regarded as a very promising sensing material. However, single indium oxide has disadvantages such as low sensitivity and poor selectivity. Constructing composite materials is an effective way to improve gas sensing performance. For example, the patent "A method for preparing a formaldehyde sensor of NiCo2O4-In2O3 composite gas-sensitive material" (CN115290704A) uses indium chloride, cobalt nitrate, nickel nitrate and urea as raw materials to prepare NiCo2O4-In2O3 composite materials by a two-step hydrothermal method. The sensor prepared by the composite material has a response value of 3.1 to 10ppm formaldehyde gas at room temperature. However, this material has a disadvantage that the improvement of the response value of the composite material is not particularly significant compared with the pure In2O3 material (whose response value to 10ppm formaldehyde gas is 2.6).

[0004] CoSnO3 is a typical perovskite structure and belongs to a p-type semiconductor. Due to its unique structure, adjustable band gap, high carrier mobility, excellent chemical stability, thermal stability and catalytic performance, these characteristics make it show certain development potential in the field of gas sensing. However, the effect of single CoSnO3 on gas detection is not ideal. The patent "n-Butanol gas-sensitive material and preparation method, n-Butanol gas-sensitive device and preparation method" (CN108609664A) uses CoSnO3 prepared by hydrothermal method combined with high-temperature calcination to detect n-butanol gas. Its sensitivity to 100ppm n-butanol gas is 18~24, and the response is relatively low. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a n-butanol gas sensor composite material and a preparation and use method thereof; the n-butanol gas sensor described in the present invention adopts a CoSnO3-In2O3 composite material to achieve high sensitivity, low detection limit and high selectivity detection of n-butanol gas.

[0006] The CoSnO3-In2O3 composite material is made by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them. The mass ratio of CoSn(OH)6 to In(OH)3 is 1:(20~500). The detection limit of the composite material for n-butanol is 20ppb, and the detection range is 20ppb~400ppm.

[0007] The preparation method of the n-butanol gas sensor composite material of the present invention is as follows: Step 1: Mixing a cobalt sulfate aqueous solution and a sodium stannate aqueous solution, wherein the molar ratio of cobalt sulfate to sodium stannate is 1:1, and after the reaction is completed, powdered CoSn(OH)6 is obtained; Step 2: The indium nitrate aqueous solution is subjected to a hydrothermal reaction to obtain powdered In(OH)3; Step 3: Mix and grind the CoSn(OH)6 obtained in step 1 and the In(OH)3 obtained in step 2, and obtain a CoSnO3-In2O3 composite material after calcination; the mass ratio of CoSn(OH)6 and In(OH)3 is 1:(20~500).

[0008] In step 1, the concentration of cobalt sulfate is 0.05 mol / L~0.2 mol / L, the concentration of sodium stannate is 0.05 mol / L~0.2 mol / L, and the reaction is stirred for 2h~6h. After the reaction, the obtained product CoSn(OH)6 is centrifuged and washed 2~5 times with water and ethanol alternately; dried at 50℃~80℃ for 10h~24h and set aside.

[0009] Step 2 includes the following contents: dissolving indium nitrate in water and stirring for 20 min to 40 min to prepare an indium nitrate aqueous solution; the hydrothermal reaction temperature is 110° C. to 180° C., and the reaction time is 8 h to 24 h; the indium nitrate concentration is 0.015 mol / L to 0.065 mol / L; the obtained product In(OH)3 is centrifuged and washed 2 to 5 times with water and ethanol alternately; and the product is dried at 50° C. to 80° C. for 10 h to 24 h for standby use.

[0010] In step 3, the calcination temperature is 300°C to 500°C; the calcination time is 1h to 4h; and the heating rate is 1°C / min to 5°C / min.

[0011] In step 2, when the concentration of the indium nitrate solution is within this range, the generated In(OH)3 precursor exhibits a good cubic morphology, which is conducive to compounding with CoSn(OH)6. When the concentration of the indium nitrate solution is <0.015 mol / L or >0.065 mol / L, the generated In(OH)3 precursor will no longer exhibit a good cubic morphology, which is not conducive to subsequent compounding, thereby affecting the response effect of the CoSnO3-In2O3 composite material to n-butanol.

[0012] The method for using the n-butanol gas sensor composite material of the present invention is as follows: Step 1: Prepare a slurry of the CoSnO3-In2O3 composite material, and apply the slurry on the surface of a substrate to form a sensing material layer to obtain a n-butanol gas sensor; The method includes the following specific contents: mixing the CoSnO3-In2O3 composite material with ethanol to prepare a slurry, ultrasonically treating for 1 min to 5 min, and uniformly coating the slurry on the surface of an alumina ceramic tube substrate to form a sensing material layer; after the ethanol evaporates, aging at 200°C to 300°C for 24h to 48h to obtain a n-butanol gas sensor; Step 2: Place the n-butanol gas sensor in the atmosphere of the gas to be tested, and keep the sensor in the operating temperature range of 175℃~325℃ under the excitation voltage of 3V~24V. a / R g The calculation method tests the response value of the sensor to the gas to be tested (where R a and R g are the resistance values ​​of the sensor in air and in the atmosphere of the gas to be measured, respectively).

[0013] The present invention adopts a coprecipitation method to prepare a CoSnO3 precursor, utilizes a one-step hydrothermal method to synthesize an In2O3 precursor, mixes, grinds and calcines the two precursors, and obtains a CoSnO3-In2O3 heterostructure composite material. The prepared CoSnO3-In2O3 heterostructure composite material has low cost, simple composite method, high sensitivity and good selectivity to n-butanol, a detection limit as low as 20 ppb, a detection range of 20 ppb to 400 ppm, and better performance than the currently reported n-butanol sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Scanning electron microscope images (SEM) of the sensing materials prepared in the comparative examples and the examples; wherein (a) represents comparative example 1, (b) represents example 2, (c) represents example 3, and (d) represents example 6; Figure 2Transmission electron microscopy (TEM) images of the sensing material prepared in Example 3; (a) and (b) are TEM images of 1% CoSnO3-In2O3 composite materials, (c) and (d) are Figure 2 (b) A partial enlarged view; Figure 3 XRD patterns of the sensing materials prepared in Comparative Examples 1, 3 and Examples 2, 3, and 6; Figure 4 The graph is a graph showing the response value of the sensor prepared by the sensing materials obtained in Comparative Example 1 and Examples 2, 3, and 6 to 100 ppm n-butanol as a function of the operating temperature; Figure 5 The gas-sensing performance test diagram of the sensor prepared by the sensing materials obtained in Comparative Example 1 and Examples 2, 3, and 6 to n-butanol gas of different concentrations (10 ppm to 400 ppm) at 250° C.; Figure 6 The transient curve of the cyclic sensing of the sensor prepared by the sensing material obtained in Example 3 to 100 ppm n-butanol at 250°C; Figure 7 Radar graphs of the response values ​​of sensors prepared from the sensing materials obtained in Comparative Example 1 and Example 3 to 100 ppm of different VOC gases at 250° C.; Figure 8 The gas-sensing performance test diagrams of the sensors prepared from the sensing materials obtained in Examples 1 to 6 at 250°C for n-butanol gas of different concentrations (5 ppm to the lower limit of detection); wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, (e) is Example 5, and (f) is Example 6; Fig. 9 This is a test chart of the gas-sensing performance of the sensor prepared with the sensing materials obtained in Comparative Examples 1 and 2 to n-butanol gas of different concentrations (5 ppm ~ detection limit) at 250°C. DETAILED DESCRIPTION

[0015] The technical scheme of the present invention is clearly and completely described below in conjunction with the embodiments and the accompanying drawings. It should be pointed out that the embodiments described in the present invention are only used to further explain and illustrate, rather than to limit the scope of application. Based on the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0016] Example 1: 0.2% CoSnO3-In2O3 composite material The n-butanol sensing material is a CoSnO3-In2O3 composite material, which is made by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them. The mass ratio of CoSn(OH)6 to In(OH)3 is 1:500.

[0017] Step 1: Dissolve 0.75 mmol of cobalt sulfate in 15 mL of deionized water to form solution A, and dissolve 0.75 mmol of sodium stannate in 15 mL of deionized water to form solution B; pour the above solution B into solution A, mix and stir for 2 h, centrifuge and wash twice with water and ethanol alternately, and dry at 50°C for 24 h to obtain purple powder CoSn(OH)6 for standby use; Step 2: Weigh 1.95 mmol of indium nitrate and dissolve it in 30 mL of deionized water, stirring for 20 min; transfer the above solution to a stainless steel autoclave lined with polytetrafluoroethylene, place it in a 150°C oven for reaction for 8 h; centrifuge and wash twice with water and ethanol alternately, and dry it in a 50°C oven for 24 h to obtain white powder In(OH)3 for standby use; Step 3: Weigh 0.2 mg of the powder in step 1 and 100 mg of the powder in step 2, mix and grind, put into a muffle furnace, heat up at a rate of 1°C / min, and calcine at 300°C for 4 hours to obtain a 0.2% CoSnO3-In2O3 composite sensing material.

[0018] The n-butanol gas sensor was prepared using 0.2% CoSnO3-In2O3 composite material. The specific method is as follows: Step 1: Weigh 3 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonic treatment is performed for 1 min. A proper amount of slurry is taken with a pipette and dropped onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base with solder; Step 3: Place the prepared sensor on an aging bench and age it at 200°C for 48 hours to obtain a n-butanol gas sensor based on 0.2% CoSnO3-In2O3 composite material.

[0019] Example 2: 0.5% CoSnO3-In2O3 composite material The n-butanol sensing material is a CoSnO3-In2O3 composite material, which is made by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them. The mass ratio of CoSn(OH)6 to In(OH)3 is 1:200.

[0020] Step 1: Dissolve 2 mmol of cobalt sulfate in 15 mL of deionized water to form solution A, and dissolve 2 mmol of sodium stannate in 15 mL of deionized water to form solution B; pour the above solution B into solution A, mix and stir for 4 h, centrifuge and wash 3 times with water and ethanol alternately, and dry at 60°C for 12 h to obtain purple powder CoSn(OH)6 for standby use; Step 2: Weigh 1 mmol of indium nitrate and dissolve it in 30 mL of deionized water, stirring for 30 min; transfer the above solution to a stainless steel autoclave lined with polytetrafluoroethylene, place it in a 130°C oven for reaction for 12 h; centrifuge and wash it three times with water and ethanol alternately, and dry it in a 60°C oven for 12 h to obtain white powder In(OH)3 for standby use; Step 3: Weigh 0.5 mg of the powder in step 1 and 100 mg of the powder in step 2, mix and grind, put into a muffle furnace, heat up at a rate of 2°C / min, and calcine at 400°C for 2h to obtain a 0.5% CoSnO3-In2O3 composite sensing material. The scanning electron microscope image of the composite material is shown in Figure 1 (b) shows the XRD pattern. Figure 3 shown.

[0021] The n-butanol gas sensor was prepared using 0.5% CoSnO3-In2O3 composite material. The specific method is as follows: Step 1: Weigh 3 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonicate for 2 min, and use a pipette to take an appropriate amount of the slurry and drop it onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base with solder; Step 3: Place the prepared sensor on an aging bench and age it at 250°C for 24 hours to obtain a n-butanol gas sensor based on 0.5% CoSnO3-In2O3 composite material.

[0022] Example 3: 1% CoSnO3-In2O3 composite material The n-butanol sensing material is a CoSnO3-In2O3 composite material, which is made by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them. The mass ratio of CoSn(OH)6 to In(OH)3 is 1:100.

[0023] Step 1: Dissolve 2 mmol of cobalt sulfate in 15 mL of deionized water to form solution A, and dissolve 2 mmol of sodium stannate in 15 mL of water to form solution B; pour the above solution B into solution A, mix and stir for 4 hours, centrifuge and wash 3 times with water and ethanol alternately, and dry at 60°C for 12 hours to obtain purple powder CoSn(OH)6 for standby use; Step 2: Weigh 1 mmol of indium nitrate and dissolve it in 30 mL of deionized water, stirring for 30 min; transfer the above solution to a stainless steel autoclave lined with polytetrafluoroethylene, place it in a 130°C oven for reaction for 12 h; centrifuge and wash it three times with water and ethanol alternately, and dry it in a 60°C oven for 12 h to obtain white powder In(OH)3 for standby use; Step 3: Weigh 1 mg of the powder in step 1 and 100 mg of the powder in step 2, mix and grind, put into a muffle furnace, heat up at a rate of 2°C / min, and calcine at 400°C for 2h to obtain a 1% CoSnO3-In2O3 composite sensing material. The scanning electron microscope image of the composite material is shown in Figure 1 (c) shows the transmission electron microscopy image. Figure 2 (a) and Figure 2 As shown in (b), Figure 2 (c) Proved the existence of amorphous structure CoSnO3, Figure 2 (d) The existence of In2O3 is proved, and the XRD pattern is as follows Figure 3 shown.

[0024] The n-butanol gas sensor was prepared using 1% CoSnO3-In2O3 composite material. The specific method is as follows: Step 1: Weigh 4 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonicate for 3 min, and use a pipette to take an appropriate amount of the slurry and drop it onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base; Step 3: Place the prepared sensor on an aging bench and age it at 250°C for 24 hours to obtain a n-butanol gas sensor based on 1% CoSnO3-In2O3 composite material.

[0025] Example 4: 2% CoSnO3-In2O3 composite material The n-butanol sensing material is a CoSnO3-In2O3 composite material, which is made by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them. The mass ratio of CoSn(OH)6 to In(OH)3 is 1:50.

[0026] Step 1: Dissolve 2.5 mmol of cobalt sulfate in 15 mL of deionized water to form solution A, and dissolve 2.5 mmol of sodium stannate in 15 mL of deionized water to form solution B; pour the above solution B into solution A, stir for 6 hours, centrifuge and wash 5 times with water and ethanol alternately, and dry at 80°C for 8 hours to obtain purple powder CoSn(OH)6 for standby use; Step 2: Weigh 0.6 mmol of indium nitrate and dissolve it in 30 mL of deionized water, stirring for 30 min; transfer the above solution to a stainless steel autoclave lined with polytetrafluoroethylene, place it in a 180°C oven for reaction for 8 h; centrifuge and wash it with water and ethanol alternately for 5 times, and dry it in an 80°C oven for 8 h to obtain white powder In(OH)3 for standby use; Step 3: Weigh 2 mg of the powder in step 1 and 100 mg of the powder in step 2, mix and grind, put into a muffle furnace, heat up at a rate of 5°C / min, and calcine at 500°C for 1 h to obtain a 2% CoSnO3-In2O3 composite sensing material.

[0027] The n-butanol gas sensor was prepared using 2% CoSnO3-In2O3 composite material. The specific method is as follows: Step 1: Weigh 4 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonicate for 3 min, and use a pipette to take an appropriate amount of the slurry and drop it onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base with solder; Step 3: Place the prepared sensor on an aging bench and age it at 300°C for 36 hours to obtain a n-butanol gas sensor based on 2% CoSnO3-In2O3 composite material.

[0028] Example 5: 3% CoSnO3-In2O3 composite material The n-butanol sensing material is a CoSnO3-In2O3 composite material, which is made by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them. The mass ratio of CoSn(OH)6 to In(OH)3 is 1:33.3.

[0029] Step 1: Dissolve 3 mmol of cobalt sulfate in 15 mL of deionized water to form solution A, and dissolve 3 mmol of sodium stannate in 15 mL of deionized water to form solution B; pour the above solution B into solution A, stir for 3 hours, centrifuge and wash 4 times with water and ethanol alternately, and dry at 70°C for 18 hours to obtain purple powder CoSn(OH)6 for standby use; Step 2: Weigh 0.45 mmol of indium nitrate and dissolve it in 30 mL of deionized water, stirring for 40 min; transfer the above solution to a stainless steel autoclave lined with polytetrafluoroethylene, place it in a 110°C oven for reaction for 10 h; centrifuge and wash it with water and ethanol alternately for 4 times, and dry it in a 70°C oven for 18 h to obtain white powder In(OH)3 for standby use; Step 3: Weigh 3 mg of the powder in step 1 and 100 mg of the powder in step 2, mix and grind, put into a muffle furnace, heat up at a rate of 3°C / min, and calcine at 500°C for 3 h to obtain a 3% CoSnO3-In2O3 composite sensing material.

[0030] The n-butanol gas sensor was prepared using 3% CoSnO3-In2O3 composite material. The specific method is as follows: Step 1: Weigh 4 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonicate for 4 min, and use a pipette to take an appropriate amount of the slurry and drop it onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base; Step 3: Place the prepared sensor on an aging bench and age it at 200°C for 48 hours to obtain a n-butanol gas sensor based on a 3% CoSnO3-In2O3 composite material.

[0031] Example 6: 5% CoSnO3-In2O3 composite material The n-butanol sensing material is a CoSnO3-In2O3 composite material, which is made by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them. The mass ratio of CoSn(OH)6 to In(OH)3 is 1:20.

[0032] Step 1: Dissolve 2 mmol of cobalt sulfate in 15 mL of deionized water to form solution A, and dissolve 2 mmol of sodium stannate in 15 mL of deionized water to form solution B; pour the above solution B into solution A, stir for 4 hours, centrifuge and wash 3 times with water and ethanol alternately, and dry at 60°C for 12 hours to obtain purple powder CoSn(OH)6 for standby use; Step 2: Weigh 1 mmol of indium nitrate and dissolve it in 30 mL of deionized water, stirring for 30 min; transfer the above solution to a stainless steel autoclave lined with polytetrafluoroethylene, place it in a 130°C oven for reaction for 12 h; centrifuge and wash it three times with water and ethanol alternately, and dry it in a 60°C oven for 12 h to obtain white powder In(OH)3 for standby use; Step 3: Weigh 5 mg of the powder in step 1 and 100 mg of the powder in step 2, mix and grind, put into a muffle furnace, heat up at a rate of 2°C / min, and calcine at 400°C for 2h to obtain a 5% CoSnO3-In2O3 composite sensing material. The scanning electron microscope image of the composite material is shown in Figure 1 (d) shows the XRD pattern. Figure 3 shown.

[0033] The n-butanol gas sensor was prepared using 5% CoSnO3-In2O3 composite material. The specific method is as follows: Step 1: Weigh 5 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonicate for 5 min. Use a pipette to take an appropriate amount of the slurry and drop it onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base; Step 3: Place the prepared sensor on an aging bench and age it at 280°C for 18 h to obtain a n-butanol gas sensor based on a 5% CoSnO3-In2O3 composite material.

[0034] Comparative Example 1: Unmodified In2O3 material The sensing material of n-butanol is In2O3 material, not composite.

[0035] Weigh 1 mmol of indium nitrate and dissolve it in 30 mL of deionized water, stirring for 30 min; transfer the above solution to a polytetrafluoroethylene-lined autoclave and place it in a 130°C oven for reaction for 12 h; centrifuge and wash it three times with water and ethanol alternately, and dry it in a 60°C oven for 12 h to obtain a white powder In(OH)3; The obtained powder was placed in a muffle furnace, heated at a rate of 2°C / min, and calcined at 400°C for 2h to obtain a light yellow product In2O3 sensing material. Figure 1 (a) shows the XRD pattern. Figure 3 shown.

[0036] The n-butanol gas sensor is prepared using In2O3 material. The specific method is as follows: Step 1: Weigh 4 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonicate for 3 min, and use a pipette to take an appropriate amount of the slurry and drop it onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base with solder; Step 3: Place the prepared sensor on an aging bench and age it at 250°C for 24 hours to obtain a n-butanol gas sensor based on In2O3 material.

[0037] Comparative Example 2: 7% CoSnO3-In2O3 composite material The n-butanol sensing material is a CoSnO3-In2O3 composite material, which is made by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them. The mass ratio of CoSn(OH)6 to In(OH)3 is 1:14.3.

[0038] Step 1: Dissolve 2 mmol of cobalt sulfate in 15 mL of deionized water to form solution A, and dissolve 2 mmol of sodium stannate in 15 mL of deionized water to form solution B; pour the above solution B into solution A, stir for 4 hours, centrifuge and wash 3 times with water and ethanol alternately, and dry at 60°C for 12 hours to obtain purple powder CoSn(OH)6 for standby use; Step 2: Weigh 1 mmol of indium nitrate and dissolve it in 30 mL of deionized water, stirring for 30 min; transfer the above solution to a stainless steel autoclave lined with polytetrafluoroethylene, place it in a 130°C oven for reaction for 12 h; centrifuge and wash it three times with water and ethanol alternately, and dry it in a 60°C oven for 12 h to obtain white powder In(OH)3 for standby use; Step 3: Weigh 7 mg of the powder in step 1 and 100 mg of the powder in step 2, mix and grind, put into a muffle furnace, heat up at a rate of 2°C / min, and calcine at 400°C for 2h to obtain a 7% CoSnO3-In2O3 composite sensing material.

[0039] The n-butanol gas sensor was prepared using 7% CoSnO3-In2O3 composite material. The specific method is as follows: Step 1: Weigh 4 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonicate for 3 min, and use a pipette to take an appropriate amount of the slurry and drop it onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base; Step 3: Place the prepared sensor on an aging bench and age it at 250°C for 24 hours to obtain a n-butanol gas sensor based on 7% CoSnO3-In2O3 material.

[0040] Comparative Example 3: CoSnO3 material The sensing material of n-butanol is CoSnO3 material, not composite.

[0041] 2 mmol of cobalt sulfate was dissolved in 15 mL of deionized water to form solution A, and 2 mmol of sodium stannate was dissolved in 15 mL of deionized water to form solution B; the above solution B was poured into solution A, stirred for 4 h, centrifuged and washed 3 times with water and ethanol alternately, and dried at 60 ° C for 12 h to obtain purple powder CoSn(OH)6; The obtained powder was placed in a muffle furnace, heated at a rate of 2°C / min, and calcined at 400°C for 2h to obtain a black product CoSnO3 sensing material. Figure 3 As shown, Figure 3 The CoSnO3 in the sample has an amorphous structure, so the corresponding XRD pattern has no sharp characteristic peaks.

[0042] The n-butanol gas sensor is prepared using CoSnO3 material. The specific method is as follows: Step 1: Weigh 4 mg of the sensing material sample prepared by the above method and add it to 10 µL of ethanol to make a slurry. Ultrasonicate for 3 min, and use a pipette to take an appropriate amount of the slurry and drop it onto the surface of the alumina ceramic tube to form a uniform sensing material layer. Step 2: After it is dried naturally, pass the Ni-Cr heating wire through the alumina ceramic tube and solder it to the six-legged base with solder; Step 3: Place the prepared sensor on an aging bench and age it at 250°C for 24 hours to obtain a n-butanol gas sensor based on CoSnO3 material.

[0043] Sensing performance test of gas sensor Using the static gas distribution method, under the condition of 10V excitation voltage, for the working range of 175℃ to 325℃, the sensors made of different sensing materials were tested to test the change curve of their response value to 100ppm n-butanol gas with temperature. The results are as follows: Figure 4 As shown. Figure 4 It can be found that the response value of the 1% CoSnO3-In2O3 sensor to n-butanol reaches 903.8, which is higher than the 0.5% CoSnO3-In2O3 sensor (whose response value is 344.6) and the 5% CoSnO3-In2O3 sensor (whose response value is 679.7), and is 9 times the response value of the pure In2O3 sensor.

[0044] For the sensors made of CoSnO3-modified In2O3 materials (0.5% CoSnO3-In2O3, 1% CoSnO3-In2O3 and 5% CoSnO3-In2O3) and unmodified In2O3, the responses to 10ppm, 20ppm, 30ppm, 50ppm, 80ppm, 100ppm, 150ppm, 200ppm, 300ppm and 400ppm n-butanol at 250℃ are shown as follows: Figure 5 It can be seen that with the increase of gas concentration, the response value of the sensor to n-butanol also increases accordingly.

[0045] Figure 6 The figure is a transient curve of the cyclic sensing of the sensor prepared by the 1% CoSnO3-In2O3 composite material obtained in Example 3 to 100 ppm n-butanol at 250°C. It can be seen from the figure that the response of this sensor to n-butanol has good repeatability. The response values ​​of the 1% CoSnO3-In2O3 sensor to n-butanol, n-propanol, isopropanol, ethanol, methanol, triethylamine, acetone, toluene and aniline at 250°C are as follows: Figure 7 As shown, they are 903.8, 143.4, 61.9, 63.6, 33.1, 24.2, 36.0, 6.9 and 9.4 respectively. It can be seen that the 1% CoSnO3-In2O3 sensor has good selectivity for n-butanol.

[0046] The sensor prepared from the CoSnO3-In2O3 composite material obtained in Examples 1, 2, 3, 4, 5, and 6 was tested for the response value of lower concentration n-butanol (5 ppm to the detection limit). The results are as follows: Figure 8 As shown. Figure 8 As can be seen from (a), (b), (c), (d), (e), and (f), the detection limits of the sensors based on 0.5% CoSnO3-In2O3 and 1% CoSnO3-In2O3 are as low as 20 ppb, and the response values ​​to n-butanol are 1.75 and 1.8, respectively. Fig. 9 It can be seen that the detection limit of unmodified In2O3 is 500ppb, and the detection limit of the sensor based on 7%CoSnO3-In2O3 is significantly improved to 3ppm.

[0047] Table 1 Response time, recovery time and detection limit of sensors prepared from CoSnO3-In2O3 composite materials obtained in Examples 1, 2, 3, 4, 5, 6 and Comparative Examples 1 and 2 to n-butanol at 250°C. Example Sensing Materials Response time (s) @5ppm Recovery time (s) @5ppm Detection limit (ppb) Detection limit corresponding to the response value Example 1 <![CDATA[0.2%CoSnO3-In2O3]]> 4 14 100 1.74 Example 2 <![CDATA[0.5%CoSnO3-In2O3]]> 32 20 20 1.75 Example 3 <![CDATA[1%CoSnO3-In2O3]]> 86 29 20 1.8 Example 4 <![CDATA[2%CoSnO3-In2O3]]> 7 21 50 1.68 Example 5 <![CDATA[3%CoSnO3-In2O3]]> 12 16 50 1.76 Example 6 <![CDATA[5%CoSnO3-In2O3]]> 2 22 200 1.45 Comparative Example 1 <![CDATA[In2O3]]> 225 23 500 1.63 Comparative Example 2 <![CDATA[7%CoSnO3-In2O3]]> 1 1 3000 1.51

Claims

1. A composite material for a n-butanol gas sensor, characterized in that: The composite material is a CoSnO3-In2O3 composite material, which is prepared by mixing and grinding CoSn(OH)6 and In(OH)3 and then calcining them, and the mass ratio of CoSn(OH)6 to In(OH)3 is 1:(20-500).

2. The n-butanol gas sensor composite material according to claim 1, characterized in that: The lower detection limit of the composite material to n-butanol is 20 ppb.

3. A method for preparing the n-butanol gas sensor composite material according to claim 1, characterized in that: Includes the following: Step 1: mixing a cobalt sulfate aqueous solution and a sodium stannate aqueous solution to react, and obtaining CoSn(OH)6 after the reaction is completed; Step 2: The indium nitrate aqueous solution is subjected to a hydrothermal reaction to obtain In(OH)3; Step 3: Mix and grind the CoSn(OH)6 obtained in step 1 and the In(OH)3 obtained in step 2, and obtain a CoSnO3-In2O3 composite material after calcination; wherein the mass ratio of CoSn(OH)6 to In(OH)3 is 1:(20~500).

4. The method for preparing a composite material for a n-butanol gas sensor according to claim 3, characterized in that: In step 1, the concentration of cobalt sulfate is 0.05 mol / L~0.2 mol / L, the concentration of sodium stannate is 0.05 mol / L~0.2 mol / L, and the reaction is stirred for 2h~6h to obtain CoSn(OH)6.

5. The method for preparing a composite material for a n-butanol gas sensor according to claim 3, characterized in that: Step 2 comprises the following contents: dissolving indium nitrate in water and stirring for 20 to 40 minutes to prepare an indium nitrate aqueous solution; the hydrothermal reaction temperature is 110° C. to 180° C., the time is 8 to 24 hours, and the indium nitrate concentration is 0.015 mol / L to 0.065 mol / L.

6. The method for preparing a composite material for a n-butanol gas sensor according to claim 3, characterized in that: In step 3, the calcination temperature is 300°C to 500°C, the calcination time is 1h to 4h, and the heating rate is 1°C / min to 5°C / min.

7. The method for preparing a composite material for a n-butanol gas sensor according to claim 3, characterized in that: The CoSn(OH)6 obtained in step 1 and the In(OH)3 obtained in step 2 are first centrifuged and washed 2 to 5 times with water and ethanol alternately, then dried at 50°C to 80°C for 10h to 24h, and then used in step 3 to prepare the composite material.

8. A method for using the n-butanol gas sensor composite material according to claim 1, characterized in that: Includes the following: Step 1: Prepare a slurry of the CoSnO3-In2O3 composite material, and apply the slurry on the surface of a substrate to form a sensing material layer to obtain a n-butanol gas sensor; Step 2: Place the n-butanol gas sensor in the atmosphere of the gas to be tested, under certain excitation voltage conditions, and keep the sensor in the operating temperature range of 175℃~325℃, using R a / R g The calculation method tests the response value of the sensor to the gas to be tested, where R a and R g They are the resistance values ​​of the sensor in air and in the atmosphere of the gas to be measured, respectively.

9. The method for using the composite material for n-butanol gas sensor according to claim 8, characterized in that: Step 1 includes the following contents: mixing the CoSnO3-In2O3 composite material with ethanol to form a slurry, ultrasonically treating for 1 min to 5 min, and uniformly coating the slurry on the surface of the alumina ceramic tube substrate to form a sensing material layer; after the ethanol evaporates, aging at 200°C to 300°C for 24h to 48h to obtain a n-butanol gas sensor; in step 2, the excitation voltage is 3V to 24V.

10. A n-butanol gas sensor, characterized in that: The n-butanol sensitive material in the gas sensor is the composite material according to claim 1.

Citation Information

Patent Citations

  • Co3O4 / In2O3 heterostructure nanotube and preparation method and application thereof

    CN103643350A

  • Co-Sn composite oxide ethyl alcohol sensor and preparation and application thereof

    CN105181762A

  • Preparation method of nano-indium oxide with high sensitivity to n-butyl alcohol

    CN106986375A

  • Butanol gas sensitive material and preparation method thereof, and butanol gas sensitive device and preparation method thereof

    CN108609664A

  • Preparation method of Ag-doped SnO2 gas sensitive material

    CN113008946A

Cited By

  • N-butanol sensing material and preparation method thereof

    CN122380315A